Solar Retinopathy: A Multimodal Analysis - Claudia Bruè; Cesare Mariotti; Edoardo De Franco; Yale Fisher; Jacopo Maria Guidotti; Alfonso Giovannini (Case Reports in Ophthalmological Medicine)
Purpose. Solar retinopathy is a rare clinical disturbance, for which spectral-domain optical coherence tomography (SD-OCT) findings are not always consistent. We report on two cases of solar retinopathy and discuss its differential diagnosis. Methods. This is an observational case study. Results. A 12-year-old female was referred to ophthalmology for bilateral scotoma. Visual acuity was 20/50 in both eyes. Fundus examination was unremarkable, except for slight yellowish material in the central macula, bilaterally. SD-OCT revealed juxtafoveal microcystic cavities in the outer retina, interruption of the external limiting membrane and the inner and outer segment junctions, with disorganized material in the vitelliform space. Fundus autofluorescence showed hypoautofluorescence surrounded by a relatively hyperautofluorescent ring, bilaterally. Similar clinical and morphological findings were detected in a 27-year-old male. Conclusions. Solar retinopathy has a subtle presentation and patients often deny sun-gazing. SD-OCT and fundus autofluorescence are noninvasive and useful tools for its diagnosis.